2007
DOI: 10.1016/j.ijdevneu.2007.05.006
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐induced proliferation of developing retinal cells: regulation by factors released from postmitotic cells in culture

Abstract: ATP is an important mitogen in the developing retina and its proliferative response decreases as chick retinal cells differentiate in culture. Both non-stimulated or ATP-induced proliferative response was abolished if cycling cells were cocultured with cells from older embryos or cultured with conditioned medium (CM) from postmitotic cells. The effect of CM was dose-dependent and reversible, as removal of CM from the cultures restored both basal and ATP-induced incorporation of [3H]-thymidine. The effect of CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Although MRS 2179 did not affect the growth of glial cells over the scratched area in cultures at the stages between E8C7 and E8C10, this compound blocked, in a dose-dependent manner, the increase in the incorporation of [ 3 H]-thymidine induced by 500 μM ADP in retinal cultures at E7C2 (Online Resource 2). Moreover, no effect of 50 μM ADPβS on the incorporation of [ 3 H]-thymidine in retinal cultures at E8C8 was observed, corroborating previous evidences showing that activation of P2Y 1 receptors by ATP induces the proliferation of glial progenitors in early developing, but not in more differentiated retinal cultures [20,21].…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Although MRS 2179 did not affect the growth of glial cells over the scratched area in cultures at the stages between E8C7 and E8C10, this compound blocked, in a dose-dependent manner, the increase in the incorporation of [ 3 H]-thymidine induced by 500 μM ADP in retinal cultures at E7C2 (Online Resource 2). Moreover, no effect of 50 μM ADPβS on the incorporation of [ 3 H]-thymidine in retinal cultures at E8C8 was observed, corroborating previous evidences showing that activation of P2Y 1 receptors by ATP induces the proliferation of glial progenitors in early developing, but not in more differentiated retinal cultures [20,21].…”
Section: Resultssupporting
confidence: 88%
“…Previously, Sanches et al [20] demonstrated that ATP through the activation of P2Y 1 receptors induces the proliferation of retinal progenitors in culture, an effect that could be observed until the fourth day after the onset of retinal cell cultures [21]. However, besides their effect on the proliferation of glial progenitors, several experimental data suggest that nucleotides are involved in the growth of glial cells in the reactive gliosis that occurs when adult nervous tissue is injured [33,34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations